Ẓawāhir al-Insyā’ at-Ṭalabiy Wa Ma’ānīhi al-Balāghiyyah Fī ar-Riwāyah at-Tārīkhiyyah “al-Andalusiy al-Akhīr” Li Ahmad Amin - As-Sa'idah, Rahmah; Nasiruddin, Nasiruddin; Ismail, Muhammad (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Objective- Insya Thalabi is a word or sentence that has nothing to do with honesty or lies. The purpose of this study is to find out the sentences of Insya Thalabi in the historical novel "Andalusi Akhir" by Ahmad Amin. And knowing the meanings contained in the sentence insha thalabi.   Design/Methodology/Approach- This study uses a literature research method with the data collection method used, namely written documentation. Written documentation is a method used to collect data related to the variety of sentences insha thalabi and their meanings in the final historical novel Andalusi Akhir by Ahmad Amin. And the content analysis is a data analysis method used in this study to analyze the sentences and the content of the meaning of Insha Thalabi in the novel.   Findings- The results of the research found consist of: first, Insya Thalabi's sentences contained in the novel amounted to 184 sentences consisting of amr 14 sentences, nahy 10 sentences, istifham 86 sentences, tamanna 27 sentences, and nida 47 sentences. Second, the meanings contained in the entire sentence Insya Thalabi in this novel do not all have the original meaning of the sentence but there are also a meanings that is not original in it.  Research Limitations/Implications- In this study, the researcher focuses on researching or analyzing the content of the novel "Andalusi Akhir by Ahmad Amin" with a focus on the meaning of the sentence insya thalabi contained in it.